2009
DOI: 10.1051/forest/2009065
|View full text |Cite
|
Sign up to set email alerts
|

Development of alder carr after the abandonment of wet grasslands during the last 70 years

Abstract: Keywords:aerial photograph / Alnus glutinosa (L.) Gaertn. / dendrochronology / land abandonment / secondary succession / wetland Abstract • The secondary succession of wet grasslands to communities of alder carr dominated by Alnus glutinosa was recorded in different parts of Europe during the 20th century. However, knowledge of such development of alder carr remains insufficient.• The development of alder carr was reconstructed at five sites in the Czech Republic, using historical aerial photographs and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…The significant influence of analogous environmental gradients on structure and composition of this vegetation has already been proven [4,43,44]. In addition to the just-discussed effect of distinctive site conditions, existence of alder forests is also a matter of the recent land use, secondary succession, drainage, melioration and afforestation of permanently wet meadows [45,46]. Ecological conditions of alder carr (Alnion glutinosae) and riparian alder forests (Alnion incanae) are relatively constantly interpreted in scientific literature, but unfortunately their syntaxonomy seems to be much more complicated regarding the accurate application of the nomenclatural rules, vague syntaxonomical position of the numerous associations or confused use of the communities names.…”
Section: Discussionmentioning
confidence: 99%
“…The significant influence of analogous environmental gradients on structure and composition of this vegetation has already been proven [4,43,44]. In addition to the just-discussed effect of distinctive site conditions, existence of alder forests is also a matter of the recent land use, secondary succession, drainage, melioration and afforestation of permanently wet meadows [45,46]. Ecological conditions of alder carr (Alnion glutinosae) and riparian alder forests (Alnion incanae) are relatively constantly interpreted in scientific literature, but unfortunately their syntaxonomy seems to be much more complicated regarding the accurate application of the nomenclatural rules, vague syntaxonomical position of the numerous associations or confused use of the communities names.…”
Section: Discussionmentioning
confidence: 99%
“…The observations by Douda et al (2009) revealed that the spread of such a forest in the Czech Republic predominated until the 1970s and the observed succession pathways at sites of alder carr were probably caused by local changes in the groundwater table.…”
Section: The History Of Environmental Changesmentioning
confidence: 98%
“…Sedges and perennial grasses are key components of the understory vegetation, covering 60% and 75% of the study area, respectively. The average annual precipitation ranges from 550 to 600 mm, the average yearly temperature is 8-9°C, and the average monthly temperature ranges from approximately -2°C in January to 17°C in July (Douda et al 2009). …”
Section: Study Sitementioning
confidence: 99%